(3eQhL GdZQhS aj NQhL HjZGQhSs - (3GdMSf Hf YeQ Hf GdMSf Hf MHjH, CHh eMeO, HOQ GdOjf GdMdHj,J (B779 (3g` s ((3eMeO Hf CMeO Hf GdedG GdMdHi s)
(3BNQgG (B:s
(3JQLeI TQa GdOjf CHhYHOGddg GdMSjf Hf YeQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B208 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B206 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B169s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B274 s
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT HJfg HGdgfO (B((3)2337) s
Keywords: (3GdJGQjNs